Pemberdayaan Masyarakat di Desa Nduaria Kecamatan Kelimutu melalui Kegiatan Kuliah Kerja Nyata Mahasiswa Universitas Flores - Djou, Ana Maria Gadi; Murdaningsih, Murdaningsih; Meke, Konstantinus Denny Pareira; Tibo, Angelina; Desenjaya, Ronaldus Arman (LPPM Universitas Flores, 2022)
The problems that exist in the community of Nduaria village, Kelimutu sub-district are the lack of awareness from the community about environmental hygiene, it looks like garbage is just scattered about and the world of education is the lack of additional tutoring from parents and the lack of interest and enthusiasm for children's literacy at school. From these problems, there are several work programs set by students in the Group 19 Real Work Lecture program in the village of Nduaria, namely: 1) Caring for the environment and making trash bins, 2) Working on gates to welcome the 17 August celebrations, 3) Visits schools to conduct additional tutoring and the creation of a reading garden. 4) Digital literacy to introduce village potential through digital space. The achievements of the activities obtained in this Real Work Lecture are the creation of public awareness about the importance of disposing of waste in its place so that the environment looks clean, increasing the enthusiasm of students in Nduaria village in learning and reading, and increasing promotion by the community in introducing village potential through social media.